Martian polar vortices: Comparison of reanalyses. Issue 9 (21st September 2016) - Waugh, D. W.; Toigo, A. D.; Guzewich, S. D.; Greybush, S. J.; Wilson, R. J.; Montabone, L.
Abstract: The structure and evolution of the Martian polar vortices is examined using two recently available reanalysis systems: version 1.0 of the Mars Analysis Correction Data Assimilation (MACDA) and a preliminary version of the Ensemble Mars Atmosphere Reanalysis System (EMARS). There is quantitative agreement between the reanalyses in the lower atmosphere, where Mars Global Surveyor (MGS) Thermal Emission Spectrometer (TES) data are assimilated, but there are differences at higher altitudes reflecting differences in the free‐running general circulation model simulations used in the two reanalyses. The reanalyses show similar potential vorticity (PV) structure of the vortices: There is near‐uniform small PV equatorward of the core of the westerly jet, steep meridional PV gradients on the polar side of the jet core, and a maximum of PV located off of the pole. In maps of 30 sol mean PV, there is a near‐continuous elliptical ring of high PV with roughly constant shape and longitudinal orientation from fall to spring. However, the shape and orientation of the vortex varies on daily time scales, and there is not a continuous ring of PV but rather a series of smaller scale coherent regions of high PV. The PV structure of the Martian polar vortices is, as has been reported before, very different from that of Earth's stratospheric polar vortices, but there are similarities with Earth's tropospheric vortices which also occur at the edge of the Hadley Cell, and have near‐uniform small PV equatorward of the jet, and a large increase of PV poleward of the jet due to increased stratification. Key Points: There is quantitative agreement in polar vortex structure in two Mars reanalyses There is near‐zero PV equatorward of jet core, steepest meridional gradients poleward of jet, and maximum PV is offset from the pole On monthly timescale there is an elliptical annulus of potential vorticity but shape and orientation is much more variable at shorter times